Progress in the aftermath of conflicts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Farming Systems Approach and Postconflict Reconstruction. FAO. 1998. 73 pp. ISBN 92 5 104152 0. $8.00, e 7.70 FAO Publications See FAO reference elsewhere in this section for address.